Jawabanmu

2014-06-12T17:00:55+07:00
S1 = a = u1 =15
b = 4
u2 = 15 + 4 = 19

s1 = (p(1) +5)(2(1) - q)+5q
15 = (p+5)(2-q) + 5q
15 = 2p -pq + 10 -5q + 5q
15 = 2p - pq + 10
5 = 2p - pq
s2 = u1 + u2
s2 = 15 + 19
s2 = 34

s2 = (p(2) + 5)(2(2) - q) + 5q
34 = (2p + 5)(4 -q) +5q
34 = 8p -2pq +20 - 5q + 5q
34 = 8p -2pq +20
14 = 8p-2pq

Eliminasi
2p - pq = 5 kali 2 ----> 4p - 2pq = 10
8p - 2pq = 14
4p - 2pq = 10
4p = 4
p = 1
Substitusi p = 1 ke 2p - pq =5
2(1) -1(q) = 5
2 - q = 5
q = -3

p + q = 1 +(-3)
= -2